Endovascular surgery - Moore, Wesley S.; Ahn, Samuel S. (Elsevier/Saunders, 2011)
In the 4th edition of Endovascular Surgery, Drs. Wesley S. Moore, Samuel S. Ahn, and a host of experts guide you through the latest developments in this innovative field. New procedures and special features, such as key points and case reviews, help illustrate effective patient care, and new topics such as endoscopic management of aneurismal disease and traumatic injuries review with you the latest endovascular surgical techniques. Full-text online access at www.expertconsult.com allows you to rapidly search this reference anytime, anywhere. Review basic principles and new techniques, and follow a practical, problem-solving approach to help address challenging areas. Gain greater detail and depth than other current texts, as well as fresh perspectives with contributions from new authors.